Bipolar disorder increases the risk of poor sleep quality among senior high school students - Hasan, Surilena; Junardi, Christopher Yovan (Universa Medicina, 2020)
BackgroundPatients with bipolar disorder commonly experience sleeping problems. On the other hand, sleep disturbances have been suggested as one of the symptoms that indicate the development of bipolar disorder. Considering the detrimental effect of bipolar disorder, especially in young people, this study aimed to determine the relationship between sleep quality and risk of bipolar disorder in senior high school students. MethodsA cross-sectional study was conducted involving 725 senior high school students. The instruments used were a demographic questionnaire, Young Mania Rating Scale (YMRS), MINI International Neuropsychiatric Interview (MINI ICD-10), Hypomania/Mania Symptom Checklist (HCL-32), and Pittsburgh Sleep Quality Index (PSQI). Univariate and bivariate (simple logistic regression) analyses were performed to evaluate the relation between sleep quality and the risk of bipolar disorder.ResultsAround 28% of subjects were at risk of bipolar disorder, of which 96.6% were prone to type I, and the rest were type II. Most of the participants with bipolar disorder (64%) had poor sleep quality. The percentage of participants with type I bipolar disorder that had poor sleep quality was higher than that of type II (65.3% and 28.6%, respectively). There was a significant relationship between bipolar disorder and sleep quality (OR = 2.2; 95% CI=1.581-3.087; p=0.000). ConclusionsOur study demonstrated that in senior high school students, bipolar disorder increased the risk of poor sleep quality. Assessment of sleep disturbances routinely in psychiatric interviews may improve sleep quality. Keywords: Bipolar disorder, sleep quality, senior high school student